PENINGKATAN HASIL PRODUKSI TERNAK LELE MELALUI PENERAPAN INTERNET of THINGS (IoT) DI KELOMPOK TANI MANDIRI - Gelu, Leonard Peter; Feka, Wolfhardus Vinansius; Matoneng, Ody Wolfrit; Keraf, Fransiskus Markus Pareto (Jurnal Abdi Insani, 2025)
The production of fish sales in TTU Regency currently does not meet market demand and community needs. Along with the increasing public awareness to consume fish as the main nutrient, the demand for fish in TTU Regency is also getting higher. The problems that are often faced by cultivators are the slow production process and the business management process that is still carried out manually. Cultivators have to wait a long time to carry out the harvest, while buyers hope to get it in a short time. One of the fish that is most sought after by the public to meet daily needs is catfish. The community partnership program with the Tani Mandiri Fish Cultivation Group (POKDAKAN) aims to overcome challenges in the management of catfish farming feed through the application of Internet of Things (IoT) technology. This automated feeding system improves production efficiency with scheduled feeding and real-time feed stock monitoring, thereby reducing resource wastage and creating an ideal environment for catfish growth. The method of implementing the implementation of community partnership empowerment in the POKDAKAN Tani Mandiri group can be explained as follows where the group, the government (Sub-district Head, Village Head and Agricultural Extension Team), and the joint implementation team are involved in determining the type of activities and the implementation of activities in the field. Mentoring activities are carried out by the student support team (S-1) as a means of monitoring and evaluating activities as well as a means of improving student skills and debriefing before entering the world of work. The main activities include socialization, training in cultivation techniques, feed making, and the implementation of IoT technology in aquaculture ponds. The results of this service activity provide a significant footprint for partners where this Program increases productivity, time efficiency, and profitability in a sustainable manner, while making a positive contribution to the community around the University of Timor and the border area.